Protagoras of Abdera : the man, his measure. - Ophuijsen, Johannes M. van. (Philosophia Antiqua, 2013)
Protagoras of Abdera, Socrates' older contemporary, is regarded as one of the most prominent representatives of the so-called sophistic movement. Instead of simply accepting the biased reports given by Plato and Aristotle about this sophist, the contributors to this volume review the complicated doxographical situation and make a case for Protagoras as a philosopher in his own right. Two major themes of this volume are Protagoras' relativism and his case for a moral and political ideal, both of which are contrasted with the metaphysical idealism of his future opponents in the Academy and the mundane conventionalism typically associated with the sophists. It turns out that rather than a parasitic force of intellectual subversion, Protagoras may have been a prolific and original thinker aiming at a coherent and comprehensive view of man's place in the world.